Application of simulation integrated learning model with video assisted MIKIR approach as an effort to improve understanding of earthquake mitigation. Issue 1 (1st February 2022) - Rusilowati, A; Supriyadi,; Pangestu, M H
Abstract: The research objectives (1) measure the increase in science learning outcomes and understanding of earthquake mitigation, (2) test the achievement of science learning outcomes and earthquake mitigation more than 50%, (3) describe the acceptance of the applied learning model. The research method used pre-experimental which was conducted at SMP N 2 Sedayu, Bantul Regency. The research instrument uses pretest-posttest questions and questionnaires that have been tested for validity, reliability, discriminating power and difficulty. Data analysis using N-gain, one sample t-test one party, and descriptive percentage. The results of this research are 52.5% with an average pretest value of 48.2 and a posttest of 75.4, while the results of the analysis of an increase in earthquake mitigation were 46.8%, which was obtained from an N-gain of 0.468 which calculated differently from the average value of pretest 45.5 and posttest 71.0. The results of the hypothetical science material were significantly 52.2% while for earthquake mitigation it only reached 46.8% one of the factors that influence these results, many students do not do the given simulation. The results of the student acceptance questionnaire on the learning model showed an average score of 84.72% very good category. It can be said that the applied learning model can be accepted by students.